Forest Soils—What’s Their Peculiarity? - Klaus von Wilpert (Soil Systems, 2022)
Mankind expects from forests and forest soils benefits like pure drinking water, space for recreation, habitats for nature-near biocenoses and the production of timber as unrivaled climate-friendly raw material. An overview over 208 recent articles revealed that ecosystem services are actually the main focus in the perception of forest soil functions. Studies on structures and processes that are the basis of forest soil functions and ecosystem services are widely lacking. Therefore, additional literature was included dealing with the distinct soil structure and high porosity and pore continuity of forest soils, as well as with their high biological activity and chemical soil reaction. Thus, the highly differentiated, hierarchical soil structure in combination with the ion exchange capacity and the acid buffering capacity could be described as the main characteristics of forest soils confounding the desired ecosystem services. However, some of these functions of forest soils are endangered under the influence of environmental change or even because of forest management, like mono-cultures or soil compaction through forest machines. In the face of the high vulnerability of forest soils and increased threads, e.g., through soil acidification, it is evident that active soil management strategies must be implemented with the aim to counteract the loss of soil functions or to recover them.